(untitled) (Medical Forum Monthly, 2024)
Objective: To measure effects of fructose and uric acid on superoxide dismutase and find out the relationship among them in animal model. Study Design: comparative study Place and Duration of Study: The study was conducted at Basic Medical Sciences Institute JPGMC from November 2009 to June 2010. Materials and Methods: Total forty male albino rats with an average weight of 180±2g were selected. The rats were grouped. The animals were fed on standards diet and given tap water ad libitum until treatment. The protrocols for experiment was according to institute of laboratory animal resources on life sciences,US National research council,1996 and institutional animal ethical committee(IAEC) of basic medical sciences institute, Karachi. Albino rats were divided into four groups. Group A(10) – control given only standard diet, group B(10) fed on 60%fructose with standard diet , group C(10) fed on fructose, standard diet and intraperitonially oxonic acid 250mg/kg and group D (10) only on injection intraperotonially oxonic acid 250mg/kg. At the end of study 10 ml of blood was drawn from heart of rats. Then blood was estimated for superoxide dismutase and urate done by kit methods randox-manual /Rx monza UA230/UA 233. Results: In Group C superoxide dismutase was found to be 32%(244mg/dl±2.23)which was more than control. In the same group the uric acid concentration was highly significantly correlated with control. Conclusion: The urate concentration does increase when we take fructose upto 60%in our diet .It also increase superoxide dismutase concentration. More than this value may have inverse effect on the uric acid level and its role as an antioxidant may become inversed.